PROBLEMY AKULTURACJI WYWIADU ZOGNISKOWANEGO - Daniłowicz, Paweł (Wydział Prawa i Administracji UAM, 2002)
In the discussion of focus research and its legitimacy, emphasis is put primarily upon the study participants’ reactions, views and behaviour. An attempt is made at describing and accounting for the frequent cases o f the participants’ negative attitude towards the study, despite the fact that they are offered remuneration for their participation. With the help of psychologists’ research and opinions the Author tries to pinpoint the possible reasons for the participants’ negative reception of the sessions, such as the type and decor of the room, lighting, unfamiliarity with the persons present, the obligation to speak out in public, or video recording. Additionally, suggestions are made about how to improve the participants’ comfort and reception of the study sessions.
ACULTURATION PROBLEMS IN FOCUS RESEARCH